Is cellular heterogeneity merely a confounder to be removed from epigenome-wide association studies?. (August 2017) - Holbrook, Joanna D; Huang, Rae-Chi; Barton, Sheila J; Saffery, Richard; Lillycrop, Karen A
Excitement about DNA methylation biomarkers has been tempered by a growing appreciation of the complex causal relations with cell fate. Intersample differences in DNA methylation can be partitioned into those that are independent of cellular heterogeneity and those that are caused by differential mixtures of cell types. Generally, the field has assumed that the former are more likely to be causative of disease. The latter has been considered a likely consequence of disease and a confounder to be removed. We argue that the conceptual separation of these signals is artificial and not necessarily informative about causation. DNA methylation is a very sensitive measure of cell fate mix and therefore reveals much about underlying disease etiology including aspects of causation.